2005
DOI: 10.1002/anie.200501297
|View full text |Cite
|
Sign up to set email alerts
|

The “Noncoordinating” Anion Tf2N Coordinates to Yb2+: A Structurally Characterized Tf2N Complex from the Ionic Liquid [mppyr][Tf2N]

Abstract: Not as innocent as it looks: The first anionic Tf2N− complex, [Yb(Tf2N)4]2−, has been prepared in the ionic liquid [mppyr][Tf2N] (see crystal structure; blue: N, yellow: S, gray: C, green: F, orange: Yb, red: O; mppyr=1‐methyl‐1‐propyl‐pyrrolidinium, Tf=trifloromethanesulfonyl). The coordination of the presumed noncoordinating (“innocent”) Tf2N2− ion could have a decisive influence on reactions in ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 45 publications
9
62
0
1
Order By: Relevance
“…To force the bis-(trifluoromethylsulfonyl)imide anion to coordinate to the lanthanide ion, the authors reacted Pr(Tf 2 N) 3 4 ], where mppyr is 1-methyl-1-propylpyrrolidinium ( Figure 7). 96 Here, the coordinating unit is an anionic tetrakis complex, which shows similarities with the well-known tetrakis -diketonate complexes. 97 -anions result in coordination number eight.…”
Section: Bis(trifluoromethylsulfonyl)imide Complexesmentioning
confidence: 69%
See 1 more Smart Citation
“…To force the bis-(trifluoromethylsulfonyl)imide anion to coordinate to the lanthanide ion, the authors reacted Pr(Tf 2 N) 3 4 ], where mppyr is 1-methyl-1-propylpyrrolidinium ( Figure 7). 96 Here, the coordinating unit is an anionic tetrakis complex, which shows similarities with the well-known tetrakis -diketonate complexes. 97 -anions result in coordination number eight.…”
Section: Bis(trifluoromethylsulfonyl)imide Complexesmentioning
confidence: 69%
“…125 Mudring et al reported that the divalent ytterbium ion is a stable species in a pyrrolidinium ionic liquid. 96 The redox behavior of the lanthanide complexes [Ln(Tf 2 N) 3 Tetravalent cerium is not stable in LiCl-KCl eutectic melts, because cerium(IV) is reduced by chloride ions. 127 Cerium-(IV) has a higher kinetic stability in AlCl 3 -[C 2 mim]Cl ionic liquids, but it is eventually reduced to cerium(III).…”
Section: Redox Behavior Of Lanthanidesmentioning
confidence: 99%
“…Both conformers coexist in neat RTIL, 22,32 whereas the C1 conformer is preferred in the coordination sphere around the metal ion. This is indeed seen in crystals of M(TFSA)n (M = Li, K, Ca, Sr, Ba and Yb), [25][26][27][28] and is ascribed to the dipole moment of the C1 conformer (4.3 D) being larger than that of the C2 conformer (0.0 D). The lithium ion binds not only the C1 conformer, but also the C2 conformer in the ionic liquid, unlike crystals, according to our Raman and DFT studies.…”
Section: Resultsmentioning
confidence: 88%
“…Indeed, only the C1 conformer is found in crystals of M(TFSA)n (M = Li, K, Ca, Sr, Ba and Yb). [25][26][27][28] Recently, we reported the solvation structure of the lithium ion in EMI + TFSA -studied by Raman spectra and DFT calculations. 29 These studies established that the lithium ion is four-coordinated -prefers the C1 conformer upon coordination to the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…Cs + forms therefore only ML complexes with 18-crown-6 in water (E N T 10), DMSO (E N T 0. 5 ], where PMIM indicates 1-propyl-3-methylimidazolium and mppyr -1-methyl-1-propylpyrrolidinium (Murding, et al 2005), have demonstrated that it can coordinate as a bidentate ligand via oxygen atoms forming either 6-membered or 4-membered rings: (Babai & Murding, 2006). Even the alkali ions are found to form weak bonds with N(Tf 2 ) - (Yan et al, 2010).…”
Section: Thermodynamics Of Complex Formation In Rtilmentioning
confidence: 99%